Kemitraan Produksi Benih Jagung Hibrida Antara PT. Agri Makmur Pertiwi, Agen (Grower) dan Kelompok Tani Sidodadi di Kecamatan Prambanan Kabupaten Sleman - Cahyadi, Wendy Dimas (Proceedings Series on Physical & Formal Sciences, 2021)
This research was conducted in Sumberharjo village, Prambanan district, Sleman regency, Special Region of Yogyakarta. It aims to study (1) the partnership process, (2) the determination of the partnership pattern, (3) the application of the partnership’s principles, and (4) the independence of Sidodadi Farmers with the existence of the production partnership of hybrid corn seed operated among Agri Makmur Pertiwi Inc., Agent (grower), and Sidodadi Farmers in Prambanan district, Sleman regency. This study utilized qualitative approach and the case study in Sumberharjo village. The data retrieval technique key informant was carried out purposively, namely Field Assistant and Quality Control of Agri Makmur Pertiwi Inc. in Central Java and Yogyakarta, Field Assistant of the Agent, the head as well as members of the Sidodadi farmers. Meanwhile, the data collection was done by observation, interview, and documentation, whereas the qualitative data analysis technique was obtained interactively and went on continuously until the data were saturated, and the validity of the data collected will be tested by the triangulation of the data collection method. The result of the study revealed that (1) the partnership process was gained from the stage of socialization, cooperation agreement, cultivation process, up to the crops deposition to the company, (2) the partnership pattern formed was Sub-contract and Agribusiness Operational Cooperation, (3) the partnership principles fulfilled were equality, transparency, result-oriented, responsibility, and complementarity, and (4) the independence of Sidodadi farmers had only reached the stage of independent fertilizer procurement and collective farmers’ cards management.